The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1002/icd.2017
|View full text |Cite
|
Sign up to set email alerts
|

Maternal guidance in at‐risk mother–child dyads: Associations with contextual variables

Abstract: The present study was designed to explore how maternal guidance (i.e., involvement and monitoring) is associated with parent‐level and contextual factors in unstructured and structured tasks. Participants were mothers who had histories of risk and disadvantage (mean age = 30.47) with their preschool‐aged children (aged 2–6 years; n males = 39, n females = 50). Maternal guidance was divided into two categories: directive (i.e., commands and command repetitions) and nondirective (i.e., queries, verbal prompts, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 107 publications
0
4
0
Order By: Relevance
“…Maternal sensitivity has long been considered and demonstrated to be a critical parenting dimension and has been linked to children’s socio-emotional outcomes (Bohr et al, 2018). Similarly, structuring (or scaffolding; Vygotsky, 1978) is also considered a key parenting dimension, has a long history, and is integrated in many parenting studies including those with a teaching, cognitive stimulation, or learning component (e.g., Saltaris et al, 2004; Briscoe et al, 2017). Recently in a sample of fullterm and preterm infants, Gueron-Sela et al (2015) showed that preterm infants had poorer cognitive outcomes at 12 months when their parents used lower levels of co-parental structuring at 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Maternal sensitivity has long been considered and demonstrated to be a critical parenting dimension and has been linked to children’s socio-emotional outcomes (Bohr et al, 2018). Similarly, structuring (or scaffolding; Vygotsky, 1978) is also considered a key parenting dimension, has a long history, and is integrated in many parenting studies including those with a teaching, cognitive stimulation, or learning component (e.g., Saltaris et al, 2004; Briscoe et al, 2017). Recently in a sample of fullterm and preterm infants, Gueron-Sela et al (2015) showed that preterm infants had poorer cognitive outcomes at 12 months when their parents used lower levels of co-parental structuring at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Child gender was coded as 1 = male , 2 = female . The DIQ measure has proven effective in collecting participant demographics, and has been used in past studies (e.g., Serbin et al, 1998; De Genna et al, 2006; Briscoe et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the sequential pairing of directives followed by compliance, but not overall frequencies of directives, relates to greater preschooler behavioral self-regulation (Lunkenheimer, Kemp, & Albrecht, 2013). Still, although the utility of directives is apparent, parents tend to use directives less as children progress through the preschool years (Briscoe, Stack, Serbin, Ledingham, & Schwartzman, 2016). During this time, higher use of directives, as compared to parenting behaviors that offer teaching, questioning, and child-led problem solving, may limit opportunities for regulatory development (Landry et al, 2000).…”
Section: Parenting Behaviors and Children’s Self-regulation Developmentmentioning
confidence: 99%